The Utilization of Vertical Wind Turbines for Micro Electricity Generation - Budi Riyanto; Abdi Seno; Naf'an Arifian; Sarifuddin (Asian Journal Science and Engineering, 2024)
This research is motivated by the rapidly increasing demand for electricity driven by modernization and industrialization, as well as by environmental challenges resulting from reliance on non-renewable fossil energy sources, thereby prompting the search for clean and efficient alternative energy. The aim of this study is to examine the potential and performance of vertical wind turbines as an innovative solution for micro power generation by assessing the efficiency of converting wind energy into electricity and evaluating its economic aspects. An observational research method was employed, incorporating literature review, team discussions, design processes, device construction, and the implementation of testing through both laboratory and field methods. The study was conducted at the Politeknik Pelayaran Sumatera Barat, where the turbine was installed on the roof of a classroom building in a coastal area, taking advantage of favorable geographic conditions and supportive wind characteristics. Data collection involved direct measurements of parameters such as wind speed, turbine and generator RPM, and electrical voltage over designated time intervals, thereby producing data on the variability and operational performance of the turbine. Results indicate that the vertical wind turbine is capable of generating electricity optimally despite fluctuations in wind speed, and it offers advantages in terms of installation flexibility, low operational costs, and energy efficiency with room for improvement. Consequently, the study recommends the development of enhanced aerodynamic designs and more optimal driving mechanisms to accommodate dynamic operational conditions, thereby facilitating the widespread implementation of this solution to support the decentralization of renewable energy systems, reduce reliance on fossil fuels, and strengthen the sustainability of electricity supply.